Evolution of electron phase space holes in inhomogeneous magnetic fields. Issue 5 (11th March 2017) - Kuzichev, I. V.; Vasko, I. Y.; Agapitov, O. V.; Mozer, F. S.; Artemyev, A. V.
Abstract: Electron phase space holes (EHs) are electrostatic solitary waves that are widely observed in the space plasma often permeated by inhomogeneous magnetic fields. Understanding of the EH evolution in inhomogeneous magnetic fields is critical for accurate interpretations of spacecraft data. To study this evolution, we use 1.5‐D gyrokinetic electrostatic Vlasov code (magnetized electrons and immobile ions) with periodic boundary conditions. We find that EHs propagating into stronger (weaker) magnetic field are decelerated (accelerated) with deceleration (acceleration) rate dependent on the magnetic field gradient. Remarkably, decelerating EHs are reflected at the magnetic field dependent only on EH parameters (independent of the magnetic field gradient). A magnetic field inhomogeneity results in development of a net potential drop along EHs. Our simulations suggest that slow EHs recently observed in the plasma sheet boundary layer can appear due to braking of initially fast EHs by magnetic field gradients and that a large number of even fast EHs can contribute to macroscopic parallel potential drops. Key Points: Magnetic field gradients result in electron hole acceleration or deceleration Magnetic field gradients result in a potential drop along electron hole Slow electron holes can be generated due to braking of fast electron holes by magnetic field gradients